(untitled) (Educational Dimension, 2023)
The focus of the study is on choosing the pedagogical conditions that will best prepare STEM teachers to utilize augmented reality tools in their classrooms. 20 conditions were initially proposed during a brainstorming session and were then sorted into five groups: (1) conditions relating to the material support of the educational process, (2) methods and forms of training, (3) best practices for utilizing augmented reality in education, (4) unique circumstances made in order to achieve the goal of training STEM teachers; and (5) conditions relating to the psychological and pedagogical support of students. A survey was conducted with 94 participants to determine the importance of these conditions. The processing of the survey data allowed for the selection of the following conditions: (a) accessibility of immersive digital educational resources for STEM teachers and mobile hardware for augmented reality (laptops, tablets, smartphones, augmented reality glasses, etc.), (b) inclusion of augmented reality-related topics in STEM teachers’ curricula, (c) use of research methodologies and interactive technologies in the STEM classroom, (d) having hands-on experience with the use of augmented reality technologies in STEM instruction.